Combining Virtual Reality Visual Novels and Social Stories to Support Social and Emotional Development in Children with Autism Spectrum Disorder - Katerina Atsalaki; Ioannis Kazanidis (Applied Sciences)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition affecting social interaction, communication, and emotional regulation, often requiring specialized educational approaches. Traditional teaching methods may not meet the needs of children with ASD, while visual and interactive formats tend to be more effective. This study examines the use of a virtual reality (VR) visual novel incorporating social stories to support social–emotional learning in children with Level 1 ASD. The intervention used an interactive, choice-based VR environment simulating everyday social situations. Four primary school students participated in a one-week case study, during which they engaged with the VR prototype. Teachers observed the students and provided feedback through questionnaires and interviews. Results showed high engagement with observable social communication behaviors and emotional responses in one participant but no consistent short-term changes across the group. All teachers expressed positive views, noting the tool’s visual clarity, ease of use, and alignment with ASD learners’ needs. Usability challenges were minimal but included pacing delays and difficulties managing impulsive behavior. Although limited by sample size and short duration, the findings indicate that VR visual novels are a promising and acceptable approach for practicing social–emotional skills in inclusive classrooms. Further research is needed to evaluate long-term effects and enhance adaptability.